Synthesis and thermoelectric properties of Rashba semiconductor BiTeBr with intensive texture - Xin, Jia-Zhan (Rare Metals, 2018)
Bismuth tellurohalides with Rashba-type spin splitting exhibit unique Fermi surface topology and are developed as promising thermoelectric materials. However, BiTeBr, which belongs to this class of materials, is rarely investigated in terms of the thermoelectric transport properties. In the study, polycrystalline bulk BiTeBr with intensive texture was synthesized via spark plasma sintering (SPS). Additionally, its thermoelectric properties above room temperature were investigated along both the in-plane and out-plane directions, and they exhibit strong anisotropy. Low sound velocity along two directions is found and contributes to its low lattice thermal conductivity. Polycrystalline BiTeBr exhibits relatively good thermoelectric performance along the in-plane direction, with a maximum dimensionless figure of merit (ZT) of 0.35 at 560 K. Further enhancements of ZT are expected by utilizing systematic optimization strategies.